2022
DOI: 10.1155/2022/9080396
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] CRISPR‐Cas System: An Adaptive Immune System’s Association with Antibiotic Resistance in Salmonella enterica Serovar Enteritidis

Abstract: Several factors are involved in the emergence of antibiotic-resistant bacteria and pose a serious threat to public health safety. Among them, clustered regularly interspaced short palindromic repeat- (CRISPR-) Cas system, an adaptive immune system, is thought to be involved in the development of antibiotic resistance in bacteria. The current study was aimed at determining not only the presence of antibiotic resistance and CRISPR-Cas system but also their association with each other in Salmonella enteritidis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Results showed that most isolates showed low resistance to GEN and CIP, up to (15.8%), in line with the previous findings [16,[38][39][40]. In contrast, the results were lower than those of Yang et al [33] in China.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results showed that most isolates showed low resistance to GEN and CIP, up to (15.8%), in line with the previous findings [16,[38][39][40]. In contrast, the results were lower than those of Yang et al [33] in China.…”
Section: Discussionsupporting
confidence: 87%
“…Results revealed that most isolates exhibited resistance to NAL, COT, and TET with a prevalence of 63.2% to 73.7%, which was nearly similar to the Myanmar findings of chicken meat-resistant isolates to COT up to 70.3% [ 37 ] but higher than the resistance in Salmonella isolated from raw poultry to COT in China as 56.6% [ 33 ]. High resistance to NAL and TET has previously been recorded in Korea [ 38 ] and Pakistan [ 39 ]. Results also revealed somewhat high resistance to AMP, ATM, and CHL, ranging from 36.8% to 47.4%, and high resistance to AMP and CHL was previously reported [ 33 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-associated (Cas) system is an acquired immune defense system with immune memory in prokaryotic genomes, which can effectively resist the acquisition of foreign mobile gene elements such as plasmids or phages to maintain the stability of bacterial genomes. 9 , 10 CRISPR-Cas system is one of the factors limiting the development and evolution of bacterial antibiotic resistance. 11 CRISPR-Cas is considered as a natural barrier to horizontal gene transfer and transmission of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the Me R-M system and the CRISPR-Cas system limit the antibiotic resistance of K. pneumoniae and E. coli ( 12 , 48 50 ). However, for S. enterica , although CRISPR-Cas has been shown to be associated with antimicrobial resistance ( 51 ), the Me R-M system has limited impact on genetic evolution ( 25 ). The differences in the effect of bacterial defense systems on bacterial resistance between bacteria may be related to the characteristics of the bacteria themselves.…”
Section: Discussionmentioning
confidence: 99%